Effect of Carrot Extracts on Pseudomonas aeruginosa - Abdulaali, Nadia Ibrahim (Pakistan Journal of Nutrition, 2009)
The aim of this study is to evaluate the effect of alcoholic and watery extracts of carrots on the growth of Pseudomonas aeruginosa. The effect of cold alcoholic and watery extracts of carrots on the growth of Pseudomonas aeruginosa was done by wells and filter papers methods, in addition the sensitivity of bacteria to the antibiotics as Ampicillin Tetracycline and Trimethprim on the growth of the bacteria in vitro was performed by serial dilutions of the carrot extracts. The results revealed that the treatments with carrot extracts especially the alcoholic extract was more efficient to inhibit the growth of Pseudomonas aeruginosa in vitro.